The sexually-selected sperm hypothesis: sex-biased inheritance and sexual antagonism. - Pizzari, T; Birkhead, T (2002)
When females are inseminated by more than one male (polyandry) sexual selection continues after insemination in the form of sperm competition and cryptic female choice. The sexually-selected sperm hypothesis proposes that, under the risk of sperm competition, additive variation in male traits determining fertilising efficiency will select for female propensity to be polyandrous in order to increase the probability of producing sons with superior fertilising efficiency. Two factors complicate this prediction: sex-biased transmission of male fertilising efficiency traits and sexual antagonism of sex-limited traits, fostered by sex-biased inheritance. Here, we (i) review the evidence that male traits contributing towards fertilising efficiency are heritable through sex-biased mechanisms, and (ii) explore the evolutionary implications for male and female reproductive strategies caused by both sex-biased transmission and sexual antagonism of fertilising efficiency traits. Many male fertilising efficiency traits are heritable through sex-biased mechanisms and may not necessarily increase female fitness. The predictions of the sexually-selected sperm hypothesis change dramatically under these different mechanisms of inheritance of fertilising efficiency traits, and different fitness pay-offs derived by females from the expression of such traits. Both sex-biased control of fertilising efficiency and sexual antagonism may also be important in explaining the maintenance of the genetic variance and selection potential of fertilising efficiency. We propose that a useful approach to test the sexually-selected sperm hypothesis is to combine studies which identify behavioural and physiological mechanisms explaining variation in reproductive success with artificial selection experiments to infer the underlying evolutionary patterns.